A Systematic Review on Education for Sustainable Development: Enhancing Tve Teacher Training Programme - Chinedu, Caleb Chidozie; Wan-Mohamed, Wan Azlinda; Ogbonnia, & Ajah Abdurrahman (Journal of Technical Education and Training, 2018)
As the call for the advancement of TVET deepens, and as skill requirement for vocations transcends traditional job requirements due to technological advancement and innovation. It becomes imperative that workers in the industrial and vocational ambits of nations develop the requisite skills and capacities for work in the 21st century that adheres to sustainable standards and meets market needs also. Thereby, contributing to societal wellbeing and community development. To achieve this goal, teachers in Technical and Vocational Education (TVE) have a crucial to play as they will be responsible for the training of workers and developing their skills and capacities for work necessary to improving societal well-being and community development. The challenge is that technical and vocational teachers are not being trained to develop capabilities for Sustainability. Using a systematic literature review, this paper critically examines the extant literature on education for sustainable development and provides a synthesis of the literature in identifying the shared message that SD and ESD models attempt to represent. Furthermore, the paper discusses the factors that foster societal well-being and community development through an ESD perspective. Conclusively emphasis is paid on the unique and significant role that technical and Vocational teachers can play in contributing towards the transition to sustainable development. Consequently, this paper culminates with an analysis of the various ways TVE can help contribute towards societal wellbeing and community development if SD is rightly integrated within TVE teacher training programs.